ИЛМИЙ МАТНЛАРДА БАЪЗИ АНТРОПОМОРФИК МЕТАФОРАЛАРНИНГ СОЦИОЛИНГИВИСТИК ТАҲЛИЛИ - Насруллаева, Г. (SCIENCE and SOCIETY, 2021)
The article analyzes the linguistic, sociolinguistic, and cognitive-pragmatic characteristics of some anthropomorphic metaphors in scientific texts. The advantages of studying anthropomorphic metaphors based on scientific texts are analyzed in world and Uzbek linguistics. Anthropomorphic metaphors are considered as the main means of increasing the impact of scientific and economic texts.
Keywords: anthropomorphic metaphor of a scientific text; popular science speech; colloquial situation; society; language; sociolinguistics; pragmatics